2008
DOI: 10.1590/s1980-57642009dn20200010
|View full text |Cite
|
Sign up to set email alerts
|

Textual reading comprehension and naming in Alzheimer's disease patients

Abstract: Among linguistic-cognitive failures, the retelling of stories and lexical disorders occur from the onset of AD. Recent studies have discussed whether lexical failures in AD patients include naming actions.ObjectivesThe aims of this study were to verify naming and reformulation of action difficulties in AD patients and their relationship with the retelling of stories. Our main questions were: Are there two linguistic abilities impaired in the early stages of AD? Is there some correlation between the capacity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
5
0
3
Order By: Relevance
“…Remarkably, anatomical and functional alterations, such as the thinning of the ganglion cell and retinal nerve fiber layers [ 26 ], the presence of protein aggregates, and glial activation [ 27 , 28 , 29 ] can be detected in the postmortem evaluation of the retina in AD patients and animal models, thus strengthening the idea that the retina could be exploited in early AD diagnosis. Moreover, visual deficits, including difficulty reading [ 30 ], depth perception [ 31 ], and color recognition [ 32 ], are also reported in the early stages of AD. Changes in retinal structure and function have been reported in other neurodegenerative disorders, such as Parkinson’s disease (PD) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, anatomical and functional alterations, such as the thinning of the ganglion cell and retinal nerve fiber layers [ 26 ], the presence of protein aggregates, and glial activation [ 27 , 28 , 29 ] can be detected in the postmortem evaluation of the retina in AD patients and animal models, thus strengthening the idea that the retina could be exploited in early AD diagnosis. Moreover, visual deficits, including difficulty reading [ 30 ], depth perception [ 31 ], and color recognition [ 32 ], are also reported in the early stages of AD. Changes in retinal structure and function have been reported in other neurodegenerative disorders, such as Parkinson’s disease (PD) [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, visual deficits, including difficulty reading (Rinaldi et al, 2008), depth perception (Mendez et al, 1996), and color recognition (Della Sala et al, 2000), are also reported in the early stages of AD. All these efforts aim to find specific biomarkers and tools for AD diagnosis at earlier stages, possibly when synapses and neuronal functions are not yet compromised, allowing pharmacological and clinical interventions (Frisoni et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Related research efforts have so far focused on language tests for the initial stages of AD with respect to the singleword lexical retrieval and the assessment of textual reading and lexical production paradigms [3], [4]. Most of them overemphasize memory dysfunction [5] to the neglect of problems arising exclusively from language [6].…”
Section: Introductionmentioning
confidence: 99%